Psychotherapy boosting future risk research: the role of radical masculinities in social polarisation from a trauma-informed perspective - Erzsébet Fanni Tóth; Kamila Midor; Enikő Darabos (European Journal of Futures Research)
Abstract This paper examines the potential integration of trauma-informed practices and Critical Studies on Men and Masculinities (CSMM) into global and European risk research, with a focus on foresight methodologies. It explores how the complex interplay between untreated trauma, rapid resource loss, radicalisation, and rigid masculine norms can potentially escalate societal risks. The study argues for the adoption of a more holistic approach in risk assessment and future planning, incorporating insights from trauma studies, masculinity research, and psychotherapy. The paper discusses the value of participatory foresight methods in capturing diverse perspectives and lived experiences, particularly those affected by toxic masculinity and radicalisation. We highlight the importance of considering intersectionality and the compounded traumas that may arise from the interaction of extremist masculine norms with other social factors. Current findings suggest that including psychotherapy scientists and practitioners in risk research could provide valuable insights into the psychological mechanisms underlying trauma, meaning-making, and identity formation. By adopting this interdisciplinary approach, the paper proposes that risk researchers may develop more comprehensive and nuanced understandings of societal risks, leading to more effective strategies for addressing the complex challenges posed by radicalisation, radical masculinity/ies, and the associated traumas in an increasingly uncertain world.